(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, we can see that the development of domestic tourism in our country from year to year, including the development of various types of domestic tourism, including pilgrimage tourism, and the work of our President in this area, laws and regulations, and also the introduction of several decrees in the development area.